Performance of Samba Wheat Variety by Adopting Production Technology in Western Zone of Tamil Nadu - kumar, S. Saravana; Alagesan, P. (Indian Journal of Hill Farming, 2018)
A study was conducted in western zone of Tamil Nadu, India to assess the performance of samba wheat variety HW 1095 vs CO (W) 1 in Talavadi hilly regions. A total of 40 frontline demonstrations were laid out at farmer’s field to demonstrate the production potential of samba wheat during Rabi season from 2010 - 2011 to 2011 - 2012. The performance of HW 1095 was superior in test weight and yield over farmer practice in all40 locations. The farmers harvested an average grain yield of 39.6 qha-1 with the highest grain yield of 40.9 qha-1 and the lowest grain yield of 38.6 qha-1 with an yield advantage of15.06 per cent over the existing variety CO (W) 1 in all locations. The productivity of wheat per unit area has been increased by adopting appropriate scientific managementpractices with a suitable variety. The result reveals that the samba wheat variety was accepted by the farmers mainly because of its yield and yield attributes by adopting scientific production technologies.